Pengaruh Waktu Perendaman Terhadap Penyerapan Asam Urat Menggunakan Membran Molecularly Imprinted Conducting Polimers (MICPs) - Nilu Gussarsi; Budhi Oktavia; Alizar Ulianas (Jurnal Periodic Jurusan Kimia UNP, 2023)
Abstract –  Molecularly Imprinted Conducting Polymers (MICPs) are polymers that have cavities that can conduct electricity. Cavities in the polymer result from template removal. The method used for the synthesis of MICPs membrane is the photopolymerization method using Ultra-Violet light. Determination of uric acid levels in solution can be analyzed using a UV-Vis spectrophotometer and in blood using an easy touch. Meanwhile, to determine the electrical conductivity using a four point probe (FPP). Based on the research, it was found that the uric acid MICPs membrane had optimum absorption at a contact time of 24 hours, with an absorption capacity of 0.532 mg/g. The uric acid MICPs membrane can absorb uric acid molecules in human blood with an absorption capacity of 0.57 mg/g according to blood pH by easy touch testing. The results of this study indicate that the MICPs membrane can absorb uric acid both in solution and in blood.